2018
DOI: 10.1038/s41598-018-28862-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut Sphingolipid Composition as a Prelude to Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) remains a major challenge in neonatology. Little is known about NEC pathophysiology apart from the presence of pre-event gut dysbiosis. Here, we applied broad range metabolomics to stools obtained 1–5 days before NEC developed from 9 cases (9 samples) and 19 (32 samples) controls matched for gestational age at birth and birth weight. The 764 identified metabolites identified six pathways that differ between cases and controls. We pursued sphingolipid metabolism because cases had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 86 publications
(68 reference statements)
1
15
1
Order By: Relevance
“…In summary, the results of the study suggest further evaluation of urine tyrosine, arginine, and riboflavin as surrogate biomarkers for NEC diagnosis. Unlike the study by Rusconi et al (108), exclusion of Bells' stage I NEC cases did not change the results indicating that metabolic alterations observed in this study are detectable during suspected NEC and could be useful as early diagnostic biomarkers.…”
Section: Clinical Studies On Metabolomics In Necrotizing Enterocolitiscontrasting
confidence: 93%
See 1 more Smart Citation
“…In summary, the results of the study suggest further evaluation of urine tyrosine, arginine, and riboflavin as surrogate biomarkers for NEC diagnosis. Unlike the study by Rusconi et al (108), exclusion of Bells' stage I NEC cases did not change the results indicating that metabolic alterations observed in this study are detectable during suspected NEC and could be useful as early diagnostic biomarkers.…”
Section: Clinical Studies On Metabolomics In Necrotizing Enterocolitiscontrasting
confidence: 93%
“…The targeted metabolomics analysis revealed that sphingomyelins were significantly higher and ceramides significantly lower in NEC cases with Bells' stage II-III, but not in stage I NEC. Conclusion was that, despite the significant differences in sphingolipid metabolism observed in pre-NEC stools compared to controls, broad application of sphingolipids as predictive biomarkers needs attention (108). In summary, changes in sphingolipids and ceramides were observed in Bell's stages II and III of NEC patients, an observation that needed further evaluation as surrogate biomarkers of NEC.…”
Section: Clinical Studies On Metabolomics In Necrotizing Enterocolitismentioning
confidence: 96%
“…For instance, sphingolipids are complex lipids known for their vital role as structural components of cell membranes and activators for natural killer T cells in the hindgut (An et al, 2014; Hasegawa et al, 2017). Because sphingolipids are crucial for the integrity of hindgut mucosa to prevent pathogenic microbe translocation into the calf circulation (Rusconi et al, 2018), the greater abundance of these lipids in MET calves could have enhanced their availability for transport into colonocytes. Arachidonic acid transport into hindgut cells in MET neonates also could have served an important role as an immune signaling molecule (Hwang, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The "healthy" microbiome implies a symbiotic life of the host with "friendly" microbes which provides homeostasis and protection from adverse short-term outcome. In preterm infants, however, there is evidence that (i) systemic inflammation (sepsis) often originates from the gut, (ii) the microbiota of preterm infants develops in a highly dynamic fashion and is therefore prone to dysbiosis, an imbalance with reduced microbial diversity and deficient metabolic capacity to control potential pathogens ("enemies"), and (iii) most circulating metabolic compounds (with potential to perpetuate inflammation) are actually derived from gut bacteria [32][33][34][35]. Specific diseases, such as sepsis and NEC, are preceded by gut dysbiosis and immunological dysbalance [36,37].…”
Section: Sustained Inflammation In the Context Of Preterm Birthmentioning
confidence: 99%